Exploring the PieTree for Representing Numerical Hierarchical Data - O'Donnell, Richard; Dix, Alan; Ball, Linden J. (People and Computers XX -- Engage: Proceedings of the Human Computer Interaction 2006, 2006)
This paper describes the first full implementation and evaluation of an area-based tree visualization known as the PieTree. The PieTree was first proposed in papers in 1998 and 2000 but has never been fully implemented and evaluated. Informal evaluation was used to enhance the usability of the PieTree and compare it with the more well-known TreeMap. A controlled experiment considered parallel views' effect on task performance time. There were substantial differences between kinds of tasks and in participants' styles of use. Whilst suggesting that further development of PieTrees is worthwhile the experiments underline the importance of careful task fit.